Protection against 2-acetyl aminofluorene induced toxicity in mice by garlic (allium sativum), bitter kola (garcinia kola seed) and honey (2005)
The effects of honey (Ho) and aqueous suspensions of garlic (Allium sativum) (Ga) and bitter kola (Garcina kola seed) (Bi) on the toxicities induced by 2- acetylaminofluorene (2-AAF) a model carcinogen, were investigated in mice. The animals were dosed for seven consecutive days with Ho, Ga and Bi as dietary Supplements. They were then challenged with a single intraperitoneal (i.p.) dose of 2-AAF at 50mg/kg bd. wt on the seventh day. The degree of clastogenicity was assessed using the mouse micronucleus assay while liver damage was monitored by measüring the level of gamma glutamyltransferase (y-GT) in serum and liver homogenates respectively. The results revealed that 2-AAF induced micronuclei formation in the polychromatic Crythrocytes (PCEs) of the bone marrow by about five fold in comparison to the PCEs formed in control mice. Ho, Ga, and Bi also induced micronucleus formation on their own. However, feeding of any of Ho, Ga or Bi and the administration (i.p) of 2-AAF reduced significantly, the ability of 2-AAF to induce micronuclei formation in the Order Ho>Ga>Bi. Furthermore, 2-AAF induced y-GT activity in the serum and liver homogenate by about two and a half and three folds respectively. A combination of 2-AAF and any of GaorBi or Ho significantly decreased 2-AAF-induced activity of y-GT in the order Ho>Bi>Ga (serum) and Bi>Ga=Ho (liver). These findings suggest that honey, garlic and bitter kola protect against 2-AAF-induced y-GTactivity and micronuleated PCEs formation.